PENGARUH JAM KERJA DAN PENGALAMAN KERJA TERHADAP PENDAPATAN DAN KESEJAHTERAAN PEKERJA PADA INDUSTRI GENTENG - Widiana, I Wayan Agus; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The data used in this study are primary data, namely by distributing questionnaires to workers in the tile industry in Kediri District, Tabanan Regency. The sample used in this study was 79 tile workers in Kediri District, Tabanan Regency. The analysis technique used in this study is path analysis. The results of the study show that working hours and work experience have a positive and significant effect on the income of workers. Working hours, work experience and worker income have a positive and significant effect on the welfare of workers. Working hours and work experience indirectly affect the welfare of workers through the income of workers. This shows that the more optimal utilization of working hours and work experience possessed by workers, it will have a good impact on the increase in income received by workers to support the welfare of their families.